Annihilation of the Jewish community of Kretinga in summer and autumn 1941 - Rukšėnas, Alfredas (Genocidas ir rezistencija, 2014)
The article examines the annihilation of the Jewish community of Kretinga in summer and autumn 1941. The paper distinguishes two stages of the annihilation. The first stage was isolation of the Jews in the second half of June 1941, when around 340 Jewish men (between 14 and 60 years of age) were arrested in Kretinga Market Square on 24 June and about 540 Jewish women, children and elderly men were arrested between 26 and 27 June. The men were locked up in the synagogue, in the prison or in the police station, which, in addition to their main function, served as temporary concentration camps. Jewish women, children and elderly men (about 560 people) were forced into the small ghetto, which did not have self-government. Some data suggest that the ghetto was in Pryšmančiai Manor; other data suggest that it was in Kluonalių (Taikos) Street in Kretinga, in a former barn. Around 100 women inmates of the small ghetto were taken to the camp in Valteriškiai Village (Palanga rural area).The second stage of annihilation of the Jews was the actual extermination operations. Around 330 Jewish men were shot at the end of June 1941 in Kvecių Forest. It is likely that in August and September 1941, around 230 Jewish women, children and elderly men could have been shot and buried here also. So a total of around 560 Jews could have been buried in Kvecių Forest. Around 230 Jewish women, children and elderly men were shot or otherwise killed in Kretinga Jewish Cemetery. Seven Jewish men who were shot by the pond near the monastery in Kretinga were also buried here. So a total of around 237 members of the Jewish community of Kretinga rural area are buried here. On 12 October 1941, around 100 women of the Jewish community of Kretinga were shot in Kunigiškių Forest (Palanga rural area) together with other inmates of the camp located near Valteriškės Village, i.e. members of Palanga Jewish community. Kvecių Forest and Kretinga Jewish Cemetery are the final resting places not only of the Jews, but also of people of other nationalities suspected of being loyal to the Soviet regime. In total 43 non-Jewish people are buried in Kvecių Forest and 21 – in Kretinga Jewish Cemetery.The annihilation of the Jewish community of Kretinga in summer and autumn 1941 was a result of the collaboration between the German occupation authorities (German military commandant, civil administration, military police, and the Tilsit operational squad) and the Lithuanian authorities (municipal, public, security and criminal police and auxiliary police). Members of the Tilsit operational squad and officers of the security and criminal police of Kretinga District (Telšiai Region) take greatest responsibility for the annihilation of the Jewish community of Kretinga. These two institutions organised massacres of Jews and other people. Other institutions played a supporting role. The difference between Kretinga County and the other counties of Lithuania (e.g. Vilnius, Kaunas, Kėdainiai) is that the Lithuanian self-defence battalions were not engaged in the killing operations of Jews and other people and there were no large ghettos here like there were in Kaunas, Vilnius or Šiauliai.About 731 local residents indirectly contributed to the persecution and killing of Jews and other people in summer and autumn 1941 in Kretinga rural area and county; these were civil servants who worked at Lithuanian municipal institutions (32 persons), public police (93), security and criminal police (6), and auxiliary police (about 600 people). About 86 persons in the town and rural area of Kretinga contributed to the annihilation of Jews, specifically 4 municipal, 6 security and criminal police, 26 public police officers and around 50 members of the auxiliary police. It has been established that 242 out of 731 people carried out acts related to their indirect participation in the persecution and extermination of Jews and other people. It was also found that 242 people across Kretinga County took direct part in the extermination operations of Jews and other people, i.e. they participated in shooting and otherwise killing about 79 people, of which 11 were in the town and rural area of Kretinga.
Keywords: German occupation; Jews; Holocaust; Kretinga